Development of a dimer‐based screening system that targets PhoR, a sensor kinase of the two‐component regulatory system, in Mycobacterium tuberculosis (Indonesian Journal of Biotechnology, 2024)
The PhoR‐PhoP two‐component regulatory system, which is responsible for regulating the virulence of Mycobacterium tuberculosis, presents a promising target for the development of novel tuberculosis drugs. Disrupting the interaction of PhoR‐PhoP proteins has the potential to decrease the virulence of the bacterium, rendering it more vulnerable to immune system clearance. A dimer‐based screening system was developed to screen for inhibitors of PhoR dimerization. The coding sequence for the cytoplasmic domain of PhoR (cytoPhoR) was combined with the DNA‐binding domain of the AraC repressor coding sequence. These sequences were positioned upstream of the emerald green fluorescent protein (EmGFP), which serves as a reporter gene. and controlled by the araC promoter. The in silico investigation examined the modeling of the fusion AraC_cytoPhoR and its binding to the promoter. The plasmid construct generated, namely pAraC_PhoRMTB, was synthesized and confirmed using DNA sequencing. The confirmed plasmid was then transformed into Escherichia coli BL21(DE3). Both SDS PAGE and fluorescence analysis indicated that the transformed culture expressed the AraC‐cytoPhoR fusion protein and displayed lower relative fluorescence in comparison to the transformed culture consisting solely of the AraC DNA‐binding domain coding sequence. This reduction in fluorescence suggests that the dimer‐based screening system effectively monitors the inhibition of dimerization of cytoPhoR. These analysis findings indicate that the system is now ready for use in the screening of PhoR dimerization inhibitors.